Internal Control And Accounting System At Cv. Bintang Lima Jaya Mandiri - Santi Yopie; Caroline Hakim (Universitas Internasional Batam, 2023)
Bintang Lima Jaya Mandiri is a micro entrepreneur engaged in the furniture trade. This business has been operating for almost 10 years. This business still uses a simple organizational structure. The operational activities are only carried out by the owner and one employee. In addition, the financial recording of this business still uses the manual version which is recorded in the book. This condition can be known after conducting visits and interviews with business owners. This activity aims to apply accounting knowledge that has been learned during college to daily activities. In addition, this activity also aims to help micro-entrepreneurs to make accurate and correct financial reports that reflect the actual financial condition of their businesses. Not only in the accounting recording system, this activity also aims to clarify the internal controls on the CV. Bintang Lima Jaya Mandiri. In this activity, an accounting recording program will be designed using Microsoft Access so that business owners can easily make financial records and the system will run automatically and will provide the financial reports that are more accurate and efficient.